P090 Assortative sexual mixing patterns in male-female and male-male partnerships in Melbourne, Australia: implications for HIV and STI transmission. (30th June 2016) - Chow, Eric; Read, Tim; Law, Matthew; Chen, Marcus; Bradshaw, Catriona; Fairley, Christopher
Abstract : Background/introduction: Assortative (like-with-like) mixing pattern has become a new and important focus in HIV/STI research in recent years in order to understand the mixed sexual network. There are very limited data on sexual mixing patterns, particularly in an Australian population. Aim(s)/objectives: To understand the assortative sexual mixing patterns for age, number of partners, and condom use in male-female and male-male partnerships in Melbourne between 2011 and 2014. Methods: 1165 male-female and 610 male-male partnerships were included. Correlation between age of partners was examined by the Spearman's rank correlation. The Newman's assortativity coefficient was used as an aggregate quantitative measurement of sexual mixing of number of partners and condom use. Results: There was a strong positive correlation between age of partners in both male-female (rho = 0.709; p < 0.001), and male-male partnerships (rho = 0.553; p < 0.001). The assortative mixing pattern for number of partners was similar in male-female ( r = 0.255), and male-male partnerships ( r = 0.264). This pattern decreased over time in male-male (p = 0.034) but not in male-female ( p = 0.718) partnerships. There was a stronger assortative mixing pattern for condom use in male-male ( r = 0.517) compared to male-female ( r = 0.382) partnerships. Discussion/conclusion: Male-female and male-male partnerships have a high assortativity mixing patterns with respects for age, number of partners, and condom use. Individuals are more likely to connect with partners with of similar age and sexual experience. The sexual mixing pattern is not purely assortative; and hence it may lead to increased HIV and STI transmission in certain risk groups.